Guidelines for Professional Library / Information Educational Programs - Elsa Bitri (Türk Kütüphaneciliği)
These guidelines replace the last significant revision in 2000 and incorporate the inclusion of materials in library school curricula that reflects the developments in the provision of library and information services in the 21st century. They set the framework for the necessary objectives for library and information educational programmes: The requirements of core and useful curriculum elements to be included in teaching programmes, the faculty, staff and student requirements for these programmes and the need for the programmes to be well supported by information and orher sources.